Green Finance and its Impact on Sustainable Economic Growth : A Global Perspective (Universitas Kristen Indonesia Toraja, 2023)
This study investigates the role of green finance in promoting sustainable economic growth worldwide. It examines the adoption of green bonds, ESG investments, and renewable energy financing in developed and developing countries. The paper discusses barriers to green finance, such as regulatory challenges and market inefficiencies, while proposing strategies to enhance financial inclusion and sustainability. Key insights are drawn from case studies in Europe and Asia.